Homomorphisms of complete n-partite graphs - Robert D. Girse (International Journal of Mathematics and Mathematical Sciences)
It is shown that for every homomorphism ϕ of a graph G there exists a contraction θϕ on G¯, the complement of G, such that ϕ(G)¯=θϕ(G¯) if and only if G is a complete n-partite graph.